The Viennese Secession - Charles, Victoria (Parkstone Press International, 2011)
A symbol of modernity, the Viennese Secession was defined by the rebellion of twenty artists who were against the conservative Vienna Künstlerhaus' oppressive influence over the city, the epoch, and the whole Austro-Hungarian Empire. Influenced by Art Nouveau, this movement (created in 1897 by Gustav Klimt, Carl Moll, and Josef Hoffmann) was not an anonymous artistic revolution. Defining itself as a "total art", without any political or commercial constraint, the Viennese Secession represented the ideological turmoil that affected craftsmen, architects, graphic artists, and designers from this.